Sympathetic Blockade for the Management of Refractory Ventricular Tachycardia: A Case Report. Issue 4 (April 2021) - Bains, Kavin; Janfaza, David; Flaherty, Devon; Zeballos, Jose; Halawa, Ahmad; Tedrow, Usha; Vlassakov, Kamen
Abstract : A 64-year-old man with a history of nonischemic cardiomyopathy (NICM) presented with electrical storm (ES). Episodes of ventricular tachycardia (VT) persisted despite endocardial catheter ablations and exhaustive pharmacotherapy. We used alternating regional anesthesia techniques, left stellate ganglion block, and proximal intercostal block to reduce sympathetic input to the heart, resulting in a significant decrease in VT burden. By using alternating catheter locations, we were able to maintain continuous sympathetic blockade for 31 days and bridge the patient to a successful orthotopic heart transplant.